Dilemmas in the diagnosis of acute community-acquired bacterial meningitis - Brouwer, Matthijs C; Thwaites, Guy E; Tunkel, Allan R; van de Beek, Diederik (The Lancet (British edition), 2012)
Rapid diagnosis and treatment of acute community-acquired bacterial meningitis reduces mortality and neurological sequelae, but can be delayed by atypical presentation, assessment of lumbar puncture safety, and poor sensitivity of standard diagnostic microbiology. Thus, diagnostic dilemmas are common in patients with suspected acute community-acquired bacterial meningitis. History and physical examination alone are sometimes not sufficient to confirm or exclude the diagnosis. Lumbar puncture is an essential investigation, but can be delayed by brain imaging. Results of cerebrospinal fluid (CSF) examination should be interpreted carefully, because CSF abnormalities vary according to the cause, patient's age and immune status, and previous treatment. Diagnostic prediction models that use a combination of clinical findings, with or without test results, can help to distinguish acute bacterial meningitis from other causes, but these models are not infallible. We review the dilemmas in the diagnosis of acute community-acquired bacterial meningitis, and focus on the roles of clinical assessment and CSF examination.